2003
DOI: 10.1088/0953-2048/16/6/201
|View full text |Cite
|
Sign up to set email alerts
|

The widely variable resistivity of MgB2samples

Abstract: In this brief review, I consider a rather mundane property of MgB 2 , namely its resistivity as a function of temperature. It turns out that a comparison of resistivity data for a wide variety of samples, from single crystals to films, wires and polycrystalline bulk, is surprisingly informative. The majority of samples of MgB 2 exhibit resistivities that are much higher than the low values that are seen in a relatively small number of single crystals, bulk samples and films. In many cases, the resistivity is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
389
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(410 citation statements)
references
References 40 publications
21
389
0
Order By: Relevance
“…22 We observed that A F of the silicone oil doped sample was larger than that of the malic acid doped sample, as well as the nanocarbon doped sample. As can be seen in Table I, A F values ranged from as low as 0.111 ͑nano-C doped MgB 2 ͒ to as high as 0.249 ͑Si-doped MgB 2 ͒, depending on the dopant.…”
Section: Resultsmentioning
confidence: 65%
“…22 We observed that A F of the silicone oil doped sample was larger than that of the malic acid doped sample, as well as the nanocarbon doped sample. As can be seen in Table I, A F values ranged from as low as 0.111 ͑nano-C doped MgB 2 ͒ to as high as 0.249 ͑Si-doped MgB 2 ͒, depending on the dopant.…”
Section: Resultsmentioning
confidence: 65%
“…7 First, we consider the area fraction. This was investigated by state-of-the-art 50-nm-resolution X-ray tomography, as shown in Figure 2.…”
Section: X-ray Tomogram Analysis On Voidsmentioning
confidence: 99%
“…The reason why the low-field properties were not improved has been studied, and the lack of enhancement has been mostly attributed to porosity. 7,8 The chemical reaction between magnesium and boron results in about 30% volume reduction, and porosity is known to be difficult to avoid. However, no quantitative analysis has ever been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The active cross-sectional area fraction (A F ) values can be estimated from resistivity measurements by using Rowell's connectivity analysis [30],…”
Section: Introductionmentioning
confidence: 99%